PENINGKATAN KINERJA MESIN 2 SILINDER DENGAN PENAMBAHAN OCTANE BOOSTER PADA RON 90 - Hariyadi, Muhammad Arif; Aspiyansyah, Aspiyansyah; Harianto, Agus; Riduan, Agus Adjie (Jurnal Rekayasa Mesin, 2024)
Octane number value in fuel plays an important role in the performance of a 2 cylinder gasoline motor. This study aims to increase the octane number value by using octane booster. The method used by mixing RON 90 with octane booster to get engine performance consisting of torque, power, specific fuel consumption and efficiency. The results show that the addition of 3 ml of octane booster to 1 liter of RON 90 will provide an optimum value on the performance of a 2-cylinder gasoline motorcycle engine.